Pengaruh Pendidikan Kesehatan Tentang Bantuan Hidup Dasar (BHD) Terhadap Kesiapan Menolong di Kampung Warna warni Malang - Qusyairi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
ABSTRACT Cardiac arrest is a condition where the heart suddenly stop beating, which can cause death if help is not received immediately. First aid must be carried out quickly after confirming that the victim is experiencing cardiac arrest. Delayed basic life support can determines the final outcome of the victim's condition, whether the victim can survive or not. This research aims to determine the effect of health education about basic life support to the readiness to help in the community of Kampung Warna Warni Malang. This research design was used a quasi-experimental 1 group that received health education. A sample of 60 respondents was obtained and given a readiness questionnaire to provide the BHD pre- post test. The research results were tested using the Wilcokson Bivariate test. The results of the pre- treatment readiness research showed that the majority of respondents had low level of readiness (95%), the results of the post-treatment research showed that almost all (88.3%) had high level of readiness. Health education increased readiness to help before and after treatment,with significancy P 0.000 (p<0.05). The average level of readiness to help are increased after being given treatment. In conclusion, there is a significant difference between before and after treatment in the value of the readiness to help. Health education is an effort to persuade or invite people to take actions to maintain or even improve their own level of health. Further research is needed for more specific readiness factors. Keywords: Health Education, Readiness to help, Basic life support, BHD Volunteers